2011
DOI: 10.1371/journal.pone.0022700
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of Cell Differentiation and Migration in Mathematical Models of Caudal Embryonic Axis Extension

Abstract: Vertebrate embryos display a predominant head-to-tail body axis whose formation is associated with the progressive development of post-cranial structures from a pool of caudal undifferentiated cells. This involves the maintenance of active FGF signaling in this caudal region as a consequence of the restricted production of the secreted factor FGF8. FGF8 is transcribed specifically in the caudal precursor region and is down-regulated as cells differentiate and the embryo extends caudally. We are interested in u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 53 publications
0
46
0
Order By: Relevance
“…Cells may respond to the mechanical properties of their ECM, such as substrate stiffness, by differentiation, proliferation and/or apoptosis [22,23,31,67]. Experiments demonstrate that a specific deformation range sensed by a cell leads to a specific differentiation [10,34,69].…”
Section: Cell Differentiation Proliferation and Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…Cells may respond to the mechanical properties of their ECM, such as substrate stiffness, by differentiation, proliferation and/or apoptosis [22,23,31,67]. Experiments demonstrate that a specific deformation range sensed by a cell leads to a specific differentiation [10,34,69].…”
Section: Cell Differentiation Proliferation and Apoptosismentioning
confidence: 99%
“…To avoid such abnormal conditions, cells have to be particularized in such a way as to differentiate or proliferate in response to appropriate biological stimuli. Experiments have shown that, besides other factors [58,59], the mechanical structure of cellular micro-environments plays an important role in cell differentiation and proliferation [22,23,31,67]. For instance, Mesenchymal Stem Cells (MSCs) differentiate into specific phenotypes with high sensitivity to the tissue rigidity where they reside in.…”
Section: Introductionmentioning
confidence: 99%
“…The FGF-8-induced chemotaxis that characterizes caudal undifferentiated cells was predicted using an equation for chemotactic energy (hybrid model) or a diffusive gradient. 25 This model has the potential to be extended to understand other developmental processes displaying a similar mode of axis extension coupled to cell differentiation. Another example of a model taking into account differentiation quantifies diverse aspects involved in the progression of bone healing for moderate fracture gap sizes and fracture stability.…”
Section: Major Achievements In Computational Models Of Stem Cell Migrmentioning
confidence: 99%
“…A number of mathematical studies have addressed the formation of gradients in the absence of morphogen diffusion, for example due to proliferation (Ibanes et al 2006, Chisholm et al 2010 or migration (Harrison et al 2011) of cells. Non-diffusive patterning mechanisms can be provided by direct contacts between cells, of which the classical example is Delta-Notch signalling associated with the binding of non-diffusive Delta to the Notch receptor of neighbouring cells (Collier et al 1996).…”
Section: Modelling Morphogen Gradientsmentioning
confidence: 99%
“…Furthermore, the movement of cells can, in turn, be affected by morphogen concentrations, for example if the movement is chemotactic and morphogens act as chemotactic agents. These possibilities have recently been explored in studies combining mathematical modelling and experiments (Vasiev et al 2010, Harrison et al 2011.…”
Section: Modelling Cell Movementmentioning
confidence: 99%